A Rejoinder to the Qadiyanies : a Muslim minority in Pakistan - Ahmad, Abdul Ghafoor (Central Ahmadiyya Organisation, 1980)
Refutation of an article written by Abdul Ghafoor Ahmad against the Ahmadiyya sect and published in Muslim herald, London, April 1975.